A Critical Review of the Book Iran in Five Narratives: About National Identity, Linguistic Diversity, Mother Tongue and the Issue of Turkish Language in Iran - Naser Sedghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The study of the concept of Iran and national identity in relation to the issue of the ethnic and linguistic diversity of Iranian society is the main subject of the book “Iran in five narratives”. In the opinion of the author, our understanding of a phenomenon called Iran is a theoretical and philosophical structure, not a fixed and permanent concept. Therefore, existing understandings of national identity and Iranianness can be criticized. By referring to the ethnic-linguistic and geographical diversity of Iranian society, the author seeks to provide a pluralistic reading of the concept of Iran and national identity. Criticizing the reductionist nationalist discourse, he considers Iranianness and national identity as a category beyond the single element of being Aryan and Persian. he believes that all Iranian ethnic groups and languages ​​such as Turkish, Arabic, Kurdish, Baluchi, and Turkmen should be considered Iranian and based on that, the concept of Iran and national dignity should be redefined. Based on such a view, the author reviews and critiques the "narratives" of Shari’ati, Motahhari, Al-Ahmad, Zarrinkoob and Maskoob about the concept of Iran, national identity and the issue of linguistic diversity. In the present study, based on the method of qualitative content analysis, the narrations of the mentioned thinkers about Iran and national identity have been presented based on the author's reading and then the author's views on the concept of Iran and national identity have been studied. In the final discussion, the shortcomings of the book of Iran in Five Narratives are stated.